Encyclopedia of earthquakes and volcanoes - Gates, Alexander E., 1957-; Ritchie, David, 1952 Sept. 18- (New York : Facts on File, 2007)
Provides information on earthquakes and volcanic eruptions in various regions of the world, major quakes and eruptions throughout history, and geologic and scientific terms.
Preface: Essay on plate tectonics -- Acknowledgments -- Introduction -- Entries A-Z -- Appendix A: Chronology of earthquakes and volcanic eruptions -- Appendix B: Eyewitness accounts of major eruptions and quakes -- Appendix C: Further reading and web sites --Appendix D: Deadliest earthquakes -- Appendix E: Deadliest volcanoes -- Appendix F: Highest magnitude earthquakes -- Appendix G: Frequency of occurrence of earthquakes -- Appendix H: Magnitude v. ground motion and energy.
Ritchie's name appears first on the previous ed
Includes bibliographical references (p. 313-315) and index
Keywords: Earthquakes -- Encyclopedias; Volcanoes -- Encyclopedias